European rural peripheries revalued. Governance, actors, impacts. - (:unkn) unknown (LIT, 2016)
The volume provides an overview of research on seemingly, current and former peripheral areas and on processes of peripheralisation in Europe. Particular emphasis is given to questions of local and regional governance, to multiple actors of peripheralisation and residential revitalisation as well as to economic and ecological transformations.
Keywords: Regionalpolitik; Landesplanung; Ländlicher Raum; Regionalentwicklung; Regionalwirtschaft; Dorferneuerung; Ländliche Gemeinde; Innovation; Förderungspolitik; Mobilität; Wohnstandort; Revitalisierung; Peripherie; EU-Förderung; Klimawandel; Erneuerbare Energie